The archetypes and the collective unconscious - Jung, C. G. (Carl Gustav), 1875-1961 (Jung, C. G. (Carl Gustav), 1875-1961. Works. 1972., 1969)
Essays which state the fundamentals of Jung's psychological system: ""On the Psychology of the Unconscious"" and ""The Relations Between the Ego and the Unconscious, "" with their original versions in an appendix.